ChemInform Abstract: Effect of Local Structure Distortion on Superconductivity in Mg‐ and F‐Codoped LaOBiS2. Issue 10 (11th March 2014) - Chen, Haijie; Zhang, Ganghua; Hu, Tao; Mu, Gang; Li, Wei; Huang, Fuqiang; Xie, Xiaoming; Jiang, Mianheng
Abstract Polycrystalline samples of La1‐xMgxO1‐2xF2xBiS2 (x = 0.1—0.35) are prepared by solid state reactions of stoichiometric mixtures of La2O3, La2S3, Bi2S3, BiF3, MgF2, LaF3, MgO, S, and Bi (evacuated quartz tube, 1073 K, 10 h).